Son Dönem Türk Öykücülüğünde Göç (2015-2022) - Bahadır, Ahmet (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
Bu çalışmada Türk öykücülüğü merkeze alınarak insanlık tarihi kadar eski olan göç olgusunun edebiyattaki aksi incelenmiş; dünyada büyük bir etki uyandıran son dönem göçlerinin edebiyata ne şekilde yansıdığı tartışılmıştır. 2000’li yıllarda Amerika-Irak savaşı ile başlayan süreç Arap baharı ile devam etmiş, Suriye iç savaşı ile Türkiye yoğun göç hareketliliğinin merkezi haline gelmiştir. İlk başlarda kamplara yerleştirilen sığınmacılar sayılarının fazlalaşmasıyla birlikte şehirlere dağılmaya başlamıştır. Özellikle 2015 yılı sonrasında ülkenin birçok şehrine yerleşen bu sığınmacılar, toplumla iç içe yaşamaya başlamışlar ve onun bir parçası olmuşlardır. Son dönem Türk öykücülüğünde bu göçlerin ele alındığı, izlek olarak seçildiği ve tartışıldığı görülmüştür. Bu amaçla belirlenen edebiyat dergilerinde 2015-2022 yılları arasında yayınlanan öyküler bu bağlamda taranmış ve 80 adet öykünün göç olgusu ile bağlantılı olduğu görülmüş, belirlenen öyküler konularına göre tasnif edilmiştir. Edebiyat ve göç üzerine kavramsal bir inceleme yapılmış, Türk anlatı geleneğinde göç olgusunun tezahürü izlenmiş ve tespit edilen öyküler üzerinden göç olgusunun öyküde ele alınış biçimi incelenmiştir. Çalışmada, disiplinler arası bir yöntemle sosyoloji biliminin açılımlarından yararlanılmış; insan, kimlik ve aidiyet kavramlarının göç olgusu ile olan ilişkileri öncelenerek, öykünün bireysel ve toplumsal anlamda göçü yansıtma şekli incelenmiştir.

In this study, the reflection of the migration phenomenon, which is as old as the history of humanity, in literature has been examined by taking Turkish storytelling as the center; it has been discussed how the recent migrations, which have a great impact on the world, have been reflected in literature. In terms of the way literature deals with social problems, modern Turkish storytelling in the recent period has also turned to issues related to people, emotions and identity. The story, which has a human being at its center, has also examined how an individual copes with social problems. Fictional reality, which is woven around the city, urban life, feelings of loneliness, also has a social-oriented side. The deep connections of man with his roots and the society he lives in through migration, identity and conflict are featured in the stories. The process that started with the USA-Iraq war in the 2000’s continued with the Arab spring, and with the Syrian civil war Turkey has become the center of intense migration mobility. At first, the refugees who were placed in the camps began to disperse to the cities with increasing numbers. Especially after 2015, these ones, who settled in many cities of the country, began to live intertwined with society and became a part of it. It has been seen that these migrations have been discussed, selected as a topic and related in Turkish storytelling of the recent period. The stories published between the years 2015-2022 in the literary journals, determined for this purpose were read in this context and 80 stories were found to be related to the phenomenon of migration. The selected stories were classified according to their themes. A conceptual review on literature and migration has been made, the manifestation of the phenomenon of migration has been observed in the Turkish narrative tradition and the way in which the phenomenon of migration was handled in the story has been examined through the identified stories. In the study, the expansions of sociology science were used with an interdisciplinary method. By prioritizing the relations of the concepts of human, identity and relation with the phenomenon of migration, the way of the story reflects individual and social migration has been examined.
Migration In Recent Turkish Storytelling (2015-2022)
Keywords: Göç; Mültecilik; Eleştiri; Kimlik; Öykü